Characterization of the Glucocorticoid Receptor in Children Undergoing Cardiac Surgery*. Issue 8 (August 2018) - Flores, Saul; Cooper, David S.; Opoka, Amy M.; Iliopoulos, Ilias; Pluckebaum, Sarah; Alder, Matthew N.; Krallman, Kelli A.; Sahay, Rashmi D.; Fei, Lin; Wong, Hector R.
Abstract : Objectives: Postoperative administration of corticosteroids is common practice for managing catecholamine refractory low cardiac output syndrome. Since corticosteroid activity is dependent on the glucocorticoid receptor, we sought to characterize glucocorticoid receptor levels in children undergoing cardiac surgery and examined the association between glucocorticoid receptor levels and cardiovascular dysfunction. Design: Prospective observational cohort study. Setting: Large, tertiary pediatric cardiac center. Subjects: Children undergoing corrective or palliative cardiac surgery. Interventions: None. Measurements and Main Results: A prospective observational cohort study was conducted in 83 children with congenital heart disease. Total glucocorticoid receptor levels were measured in the peripheral WBCs using flow cytometry. In addition, blood samples were collected for total cortisol levels. The primary outcome studied was the time to being inotrope free. An increase in glucocorticoid receptor level from postoperative day 1 to postoperative day 3 was associated with a longer time to being inotrope free (hazard ratio, 0.49 [0.29–0.81]; p = 0.01) in the univariate analysis. This association remained significant after adjusting for age, weight, cardiopulmonary bypass time, cross clamp time, Risk Adjustment for Congenital Heart Surgery-1 score, and postoperative steroid use (hazard ratio, 0.53 [0.29–0.99]; p = 0.05). Postoperative day 3 glucocorticoid receptor level showed a trend to have longer time to being inotrope free (hazard ratio, 0.66 [0.42–1.02]; p = 0.0.06). The cortisol levels minimally increased during the study duration and did not correlate with glucocorticoid receptor levels. Conclusions: Increasing glucocorticoid receptor levels in peripheral WBCs of children undergoing cardiac surgery are associated with a longer time to being inotrope free. Cortisol levels minimally increased during the study duration. These results suggest that exposure to high-dose perioperative corticosteroids may suppress the hypothalamic-pituitary-adrenal axis leading to increase in glucocorticoid receptor levels in response to a low cortisol environment. Further studies are required to better delineate the interplay between glucocorticoid receptor levels, cortisol levels, corticosteroid exposure, and postoperative inotropic requirements. Abstract : Supplemental Digital Content is available in the text.